The relationship between exposure to adverse life events in childhood and adolescent years and subsequent adult psychopathology in 49, 163 adult prisoners: A systematic review. (1st September 2018) - Bowen, Katharine; Jarrett, Manuela; Stahl, Daniel; Forrester, Andrew; Valmaggia, Lucia
Abstract: There is empirical support for an association between childhood adverse life events and psychopathology in adult offenders. This systematic review aims to summarise the literature that measures the predictive value of childhood adverse life events on mental illness and personality disorders in prisoners in custody. Forty-seven studies were identified. The studies examined a total of 49, 163 participants (36, 055 males, 13, 108 females). The number of offenders in each study ranged from 43 to 16, 043. Childhood abuse and neglect were primarily examined. There was support that these subtypes of childhood adverse life events are associated with several psychiatric disorders, in particular substance abuse and psychopathy. Additionally, there were differences across male and female prisoners both in terms of the numbers of studies that looked at specific psychopathologies, and the associations between specific childhood adverse life event subtypes and future psychiatric difficulties. Methodological considerations, future research, and clinical implications are discussed. Highlights: This systematic review synthesises data of 49, 163 participants from 47 studies. Childhood abuse and neglect were the most examined form of adverse life events. Personality and mood disorders were assessed most in males and females respectively. Childhood adverse life events were associated with substance use and psychopathy.